Antiseizure medications prescribing for behavioural and psychiatric concerns in adults with an intellectual disability living in England. (May 2023) - Branford, David; Sun, James J.; Shankar, Rohit
Summary: Antiseizure medications (ASMs) are the second most widely prescribed psychotropic for people with intellectual disabilities in England. Multiple psychotropic prescribing is prevalent in almost half of people with intellectual disabilities on ASMs. This analysis identifies limited evidence of ASM benefit in challenging behaviour management and suggests improvements needed to inform clinical practice.